Effects of zeolite supplementation on parameters of intestinal barrier integrity, inflammation, redoxbiology and performance in aerobically trained subjects. Issue 1 (December 2015) - Lamprecht, Manfred; Bogner, Simon; Steinbauer, Kurt; Schuetz, Burkhard; Greilberger, Joachim; Leber, Bettina; Wagner, Bernhard; Zinser, Erwin; Petek, Thomas; Wallner-Liebmann, Sandra; Oberwinkler, Tanja; Bachl, Norbert; et al.
Abstract Background Zeolites are crystalline compounds with microporous structures of Si-tetrahedrons. In the gut, these silicates could act as adsorbents, ion-exchangers, catalysts, detergents or anti-diarrheic agents. This study evaluated whether zeolite supplementation affects biomarkers of intestinal wall permeability and parameters of oxidation and inflammation in aerobically trained individuals, and whether it could improve their performance. Methods In a randomized, double-blinded, placebo controlled trial, 52 endurance trained men and women, similar in body fat, non-smokers, 20–50 years, received 1.85 g of zeolite per day for 12 weeks. Stool samples for determination of intestinal wall integrity biomarkers were collected. From blood, markers of redox biology, inflammation, and DNA damage were determined at the beginning and the end of the study. In addition, VO2max and maximum performance were evaluated at baseline and after 12 weeks of treatment. For statistical analyses a 2-factor ANOVA was used. Results At baseline both groups showed slightly increased stool zonulin concentrations above normal. After 12 weeks with zeolite zonulin was significantly (p  < 0.05) decreased in the supplemented group. IL-10 increased tendentially (p  < 0.1) in the zeolite group. There were no significant changes observed in the other measured parameters. Conclusions Twelve weeks of zeolite supplementation exerted beneficial effects on intestinal wall integrity as indicated via decreased concentrations of the tight junction modulator zonulin. This was accompanied by mild anti-inflammatory effects in this cohort of aerobically trained subjects. Further research is needed to explore mechanistic explanations for the observations in this study.